Transformasi Digital dalam Fungsi Pengawasan Ombudsman: Implementasi E-government untuk Pelayanan Publik: Digital Transformation in the Ombudsman's Oversight Function: E-government Implementation for Public Services - Melinda Dina Gussela; Dewi Sulastri (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2025)
Digital transformation has changed the paradigm of public services in Indonesia, however the implementation of e-government presents new challenges in the form of digital maladministration that requires adaptive supervision. This research aims to analyze digital transformation in the supervisory function of the Ombudsman regarding the implementation of e-government for public services. The research method uses a qualitative descriptive approach with case studies, collecting data through in-depth interviews, participatory observation, and documentation studies analyzed using thematic analysis techniques. The research results show that the Ombudsman faces significant institutional challenges including limited human resources competent in information technology, inadequate digital infrastructure, limited budget, and non-legally binding recommendation legal force. Digital maladministration develops in the form of unresponsive systems, personal data leaks, and algorithmic discrimination. Technology-based supervision strengthening strategies include developing integrated monitoring dashboards, utilizing big data analytics and artificial intelligence, strengthening collaborative governance, increasing digital literacy, and regulatory reform. This research concludes that effective e-government supervision requires a holistic approach integrating technology, human resources, regulations, and public participation dimensions to realize digital service accountability.